2016
DOI: 10.1371/journal.pone.0166886
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia-Induced Proliferative Retinopathy: Early Interruption of Retinal Vascular Development with Severe and Irreversible Neurovascular Disruption

Abstract: Bronchopulmonary dysplasia (BPD) is a major cause of neonatal morbidity in premature infants, occurring as a result of arrested lung development combined with multiple postnatal insults. Infants with BPD exposed to supplemental oxygen are at risk of retinopathy of prematurity as well. Thus, we studied the effects of hyperoxia on the retinal vasculature in a murine model of BPD. The retinal phenotype of this model, which we termed hyperoxia-induced proliferative retinopathy (HIPR), shows severe disruption of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…We found that many factors may be involved in this Phase I of ROP, causing a greater delay in vascular development (31).…”
Section: Discussionmentioning
confidence: 77%
“…We found that many factors may be involved in this Phase I of ROP, causing a greater delay in vascular development (31).…”
Section: Discussionmentioning
confidence: 77%
“…We previously reported significant disruption of the retinal vascular development, with persistent hyaloidal vessels in B6J HIPR [ 14 ]. Comparing the B6J and B6N strains in HIPR, retinal flat mounts stained with IB4, an endothelial cell marker, were assessed at P21 and P28.…”
Section: Resultsmentioning
confidence: 99%
“…The C57BL/6N mice carry the rd8 mutation while the C57BL/6J mice carry the wild-type Crb1 gene [ 15 , 16 ]. We have recently characterized the retinopathy in the HIPR model [ 14 , 17 , 18 ]. Briefly, newborn pups are placed in a Plexiglas chamber with an oxygen controller (Pro-Ox 110; Biospherix, Lacona, NY) and exposed to 75% oxygen from birth to P14.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations